Spirituality of students with special needs in the time of COVID-19 pandemic - Chan, Cherry L. (Animo Repository, 2021)
The development of modern education has made educators become aware of not only imparting knowledge for cognitive growth, but more so in molding the child holistically to achieve their full potential. This suggests that the teaching of spirituality, which is the subjective sense of self and knowing one’s purpose and meaning in life, should be part of the school’s curriculum to foster the students’ overall well-being, particularly for those with special needs. In this time of pandemic, however, schools have shifted to online learning, so teachers now employ a different approach in imparting their lessons, while parents play a big role in the teaching and learning process of their children who are bound at home. Thus, this phenomenological study explored the spirituality of students with special needs in the time of COVID -19 pandemic. Eleven triad respondents composed of students with different types of disabilities ages 15 to 22, their respective parents and teachers, participated in this research and agreed to be interviewed via synchronous online means. By applying the seven-step approach of Colaizzi’s method in analyzing qualitative data, four main themes have emerged, which are: a) engaging in activities, b) teaching of values, c) gaining a sense of self and d) connecting with others. These main themes together with its 13 sub themes, were substantial in answering the research questions on the spiritual education practices and the effects of these practices in the lives of students with special needs in this time of pandemic. This study concluded with implications and recommendations for educators, parents, church or faith communities and for those individuals with special needs, to better understand how spirituality in education is an important element that can uplift the quality of life of persons with disabilities.